Investigation of changes in body composition, metabolic profile and skeletal muscle functional capacity in ischemic stroke patients: the rationale and design of the Body Size in Stroke Study (BoSSS). Issue 3 (13th March 2013) - Knops, Michael; Werner, Claudia G.; Scherbakov, Nadja; Fiebach, Jochen; Dreier, Jens P.; Meisel, Andreas; Heuschmann, Peter U.; Jungehülsing, Gerd J.; von Haehling, Stephan; Dirnagl, Ulrich; Anker, Stefan D.; Doehner, Wolfram
Abstract : Background: Stroke is steadily increasing in prevalence. Muscle tissue wasting and functional changes are frequently observed in stroke, but this has not been studied in detail yet. There is a lack of data to support guideline recommendations on how to target muscle wasting in stroke patients. We hypothesise that pathophysiological metabolic profiles and muscle functional and structural impairment are developing in stroke patients, which are associated with stroke severity and outcome after stroke. Methods: The Body Size in Stroke Study (BoSSS) is a prospective, longitudinal observation study that will explore associations between the metabolic profile, body tissue wasting and particular metabolic and functional changes in skeletal muscle tissue in stroke patients. Consecutive patients with acute stroke ( n = 150) will be enrolled due to lacunar or territorial ischemic infarct in the area of the middle cerebral artery. Patients will be studied at annual intervals after 12 and 24 months. For comparison, healthy controls of similar age and patients with chronic heart failure will be used as control groups. The main objective is to study changes in body composition in stroke patients. Secondary, the study will focus on changes in insulin sensitivity of adipose tissue and skeletal muscle. Furthermore, measurements of endothelial function and peripheral blood flow will provide insight in the vascular regulation in stroke patients. Conclusion: This study will be the largest observational study providing insights into the metabolic and functional changes of muscle tissue in patients with acute ischemic stroke. The new data will increase our understanding of the pathophysiologic tissue wasting in stroke disease and help to develop new therapeutic strategies.